13.1k views
2 votes
Solve this question :​

Solve this question :​-example-1
User Jobo
by
5.0k points

1 Answer

6 votes

9514 1404 393

Step-by-step explanation:

For proofs of this nature, it often works well to replace everything possible with appropriate equivalents. Here, we'll use sin² to represent sin²(A), and equivalent notation for other trig functions.

We will change the left side to the form of the right side.


\displaystyle (\tan^2-\cot^2)/(1+\cot^2)=(\sin^2-\cos^2)/(\cos^2)\\\\=((\sec^2-1)-(\csc^2-1))/(\csc^2)\\\\=(\sin^2)(\sec^2-\csc^2)\\\\=(\sin^2)/(\cos^2)-1=(\sin^2-\cos^2)/(\cos^2)\qquad\text{Q.E.D.}

__

The equivalents (identities) used are ...

1+tan² = sec²

1+cot² = csc²

1/csc = sin

sec = 1/cos

User Primo
by
5.6k points